The Perception of Organic Food Characteristics and the Demographic and Social Profile of Consumers: A Study of the Polish Market - Małgorzata Grzywińska-Rąpca; Mariola Grzybowska-Brzezińska; Dominika Jakubowska; Joanna Katarzyna Banach (Foods)
The aim of the research was to determine the relationship between the perception of organic food characteristics and the demographic and social profile of consumers on the Polish market. The research focused on the general characteristics and features of plant and animal products offered on the organic food market compared to conventional food. The study was conducted on a sample of 1020 respondents from different regions of Poland using structural equation modelling, which allowed for the assessment of regression and covariance relationships between variables. The models allowed an in-depth assessment of the relationships between several variables and the identification of latent factors. The results of the study showed that demographic (gender and age) and economic (income and expenditure on organic food) characteristics of Polish consumers significantly influence consumer perceptions and preferences towards organic food. Women were more likely to emphasise the importance of sensory attributes (e.g., freshness and taste), while consumers with higher incomes appreciated the organic benefits of products, especially animal products (e.g., no preservatives or hormones). Surprisingly, education was not found to be a significant differentiator in the perception of organic products. The study also provided important insights for the producers and marketers of organic food, highlighting the need to differentiate marketing strategies according to the demographic and social profile of consumers.